ANALISIS WAKTU ANTRE DAN MODEL ANTREAN CHECK-IN COUNTER BAGASI TERHADAP KEPUASAN PENUMPANG PENERBANGAN MASKAPAI X PADA TERMINAL 3 BANDARA SOEKARNO HATTA - Ubaydillah Al Farizy (Jurnal Riset Multidisiplin Edukasi, 2026)
This research analyzes the queuing time and queuing model at the X airline passenger baggage check-in counter at Terminal 3 of Soekarno-Hatta Airport and its influence on passenger satisfaction. The research results show that the average queue time at the check-in counter varies between 7 to 25 minutes, depending on peak hours. Some factors that influence queue time include the number of passengers arriving at the same time, the availability of check-in staff, and the number of counters open. Increasing the number of check-in counters and staff skills can increase queue time efficiency and passenger satisfaction.